Factors Affecting Adoption of Sustainable Soil Management Practices among Fluted Pumpkin Producers in Ikorodu, Lagos State - Omowumi A. Olowa, Olatomide W. Olowa; Ijiyokun, A.O., Akinkunmi A. Falade (European Journal of Sustainable Development, 2019)
Proper soil management is germane to sustainable vegetable production. The greatest threat to sustainable agricultural productivity is the declining soil productivity. The reason for this declining soil productivity might not be unconnected with the soil management practices by farmers. This study attempts to isolate factors that are contributing to vegetable farmers’ adoption of soil management practices. Primary data were collected from purposively selected 120 fluted pumpkin vegetable farmers, adopting pre-tested semi-structured interview schedule in Ikorodu Local Government Area. This is predicated on the facts that Ikorodu environment seems to be well adapted for fluted pumpkin production as many hectares of land are cultivated to fluted pumpkin by hundreds of small holders. Probit regression model was used to isolate factors affecting the adoption of sustainable soil management practices. Overall, the model predicted 85.76% of the sample correctly. The findings of the study revealed that number of economically active family members, farmers’ education, livestock holding, membership in farmer’s group and credit availability were significantly positive while age of farmer negatively affect adoption of sustainable soil management practice. A unit increased in economically active family members, years of education and livestock standard unit would increase the probability of adoption of technology by 21.3, 5.8 and 7.6% respectively. Likewise, if farmers were made member in the groups and credit made available, the probability of adoption of technology would increase by 46.2 and 46.3% respectively. But a unit increase in the age of household head would decrease the level of adoption by 1.4% indicating old aged farmers do not adopt innovative technologies in agriculture. Keywords: Lagos, adoption, probit, sustainable soil management, vegetable, fluted pumpkin